GAMBARAN DUKUNGAN KELUARGA PADA PASIEN DM TIPE 2 DALAM MENJALANKAN 4 PILAR PENGELOLAAN DM RUANGAN POLI PD RS BHAYANGKARA MANADO - Sintya Mokodongan; Nelfa F. Takahepis; Sarwan Sarwan (Pusat Riset dan Inovasi Nasional, 2022)
Diabetes Mellitus is known as a silent killer disease because it is often not known by the sufferer and when it is known that complications have occurred to the eye (Diabetic Retinopathy), heart (diabetic chediomyopathy), repeated infections can occur, ulcers that do not heal and even amputation of fingers/toes. The design of this research is descriptive analytical with a cross sectional approach. The sample in this study were 30 people using accidental sampling. Data was collected by distributing questionnaires. Furthermore, the data were collected and tested using the chi-square test with a significance level of Asymp.ig.(p-value) = 0.000, where the p-value is smaller than the value of = 0.05. The results of the study where there was good family support with good management of 4 pillars as many as 17 respondents and good family support with poor management of 4 pillars as many as 1 respondent. While for poor family support with good management as many as 1 respondent and poor family support with poor management of 4 pillars as many as 11 respondents. The conclusion in this study is that there is a description of family support for type 2 DM patients in carrying out the 4 pillars of managing DM in the poly room at Bhayangkara Hospital, Manado